Atomic force microscopy of virus shells. (15th April 2017) - Moreno-Madrid, Francisco; Martín-González, Natalia; Llauró, Aida; Ortega-Esteban, Alvaro; Hernando-Pérez, Mercedes; Douglas, Trevor; Schaap, Iwan A.T.; de Pablo, Pedro J.
Abstract : Microscopes are used to characterize small objects with the help of probes that interact with the specimen, such as photons and electrons in optical and electron microscopies, respectively. In atomic force microscopy (AFM), the probe is a nanometric tip located at the end of a microcantilever which palpates the specimen under study just as a blind person manages a walking stick. In this way, AFM allows obtaining nanometric resolution images of individual protein shells, such as viruses, in a liquid milieu. Beyond imaging, AFM also enables not only the manipulation of single protein cages, but also the characterization of every physicochemical property capable of inducing any measurable mechanical perturbation to the microcantilever that holds the tip. In the present revision, we start revising some recipes for adsorbing protein shells on surfaces. Then, we describe several AFM approaches to study individual protein cages, ranging from imaging to spectroscopic methodologies devoted to extracting physical information, such as mechanical and electrostatic properties. We also explain how a convenient combination of AFM and fluorescence methodologies entails monitoring genome release from individual viral shells during mechanical unpacking.